Relationship between late preterm birth and expression of attention-deficit hyperactivity disorder in school-aged children: clinical, neuropsychological, and neurobiochemical outcomes - Ben Amor L; Chantal S; Bairam A (Research and Reports in Neonatology, 2012)
L Ben Amor,1,2 S Chantal,3 A Bairam41Department of Psychiatry, Hotel Dieu de Levis, 2Department of Psychiatry, Laval University, 3Enfant Jesus Hospital, 4Department of Paediatrics, Laval University, Quebec, CanadaAbstract: Attention-deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder in school-aged children, and prematurity is a recognized risk factor. Late-preterm birth, which represents 75% of premature births, is associated with ADHD symptoms, impaired cognitive performance, and behavior problems. However, little is known of the characteristics of ADHD associated with late prematurity. The purpose of this study was to compare the clinical, neuropsychological, and neurobiochemical characteristics associated with late-preterm ADHD with those of at-term ADHD.Methods: Eighty-six children with ADHD, aged 5–13 years, were recruited. They included 20 late-preterm children with ADHD and 66 at-term children with ADHD. The Diagnostic Interview Schedule for Children-IV and the Continuous Performance Test (CPT) were used to evaluate their clinical and neuropsychological characteristics. Proton magnetic resonance spectroscopy was used to measure the ratio of metabolites (glutamate, choline, and N-acetyl-aspartate) to creatine in both the prefrontal and striatal regions as well as the left cerebellum.Results: The groups did not differ in regards to clinical outcomes. However, the ADHD late-preterm group had worse omissions and commissions T-scores on CPT (P ≤ 0.05) than the ADHD at-term group. The ADHD late-preterm group also had lower ratios of glutamate in the left prefrontal cortex than the ADHD at-term group (P ≤ 0.05).Conclusion: Among children with ADHD, those born at late preterm have lower attention scores as evaluated by CPT and are associated with lower relative concentrations of glutamate in the prefrontal region than those born at term. Etiological factors could play a role in the expression of ADHD.Keywords: attention-deficit hyperactivity disorder, preterm, neuropsychological, risk factors, magnetic resonance spectroscopy, glutamate, prefrontal cortex